The application of niobium and tantalum oxides for implant surface passivation. - Starikov, V. V.; Starikova, S. L.; Mamalis, A. G.; Lavrynenko, S. N.; Ramsden, Jeremy J. (Jointly by, Collegium Basilea (Institute of Advanced Study) and Association of Modern Scientific Investigation., 2007)
Despite the advantages of ceramics, with their high corrosion stability in vivo, most medical implant constructions are still made from metals [1]. To increase the corrosion stability of metals, different coatings are applied to the implant surfaces, typically such coatings are the oxides of the metals in the implants [2]. For an oxide film to have protective properties it must satisfy the following requirements: • to be unbroken and pore-free; • to have good adhesion with the metal; • to have a thermal expansion constant near to the value for the metal; • to be chemically inert in different environments; • to be hard and have minimal wear under load. The oxides of metals such as Al, Ti, Zr, Nb and Ta satisfy all these properties to some degree [3–5]. Indeed, some of these metal oxides are used in medicine independently without a metal substrate, such as implant constructions from sapphire (a single-crystal modification of Al2O3) [6, 7]. Titanium is the most widely used material for medical implant manufacture [8]. Its chemical passivity is provided by the oxide film (TiO2), covering the entire free surface; a result of titanium contact with air. But titanium is unable to satisfy all the requirements necessary for an implant material because of its insufficient corrosion stability [9–11]. The application of combined implants consisting of a metal base and a ceramic coating also does not give a complete solution to the problem, because of the low adhesion strength and fragility of ceramic coatings [12, 13].
Keywords: anodic oxides; coating; implants; niobium; tantalum